2021
DOI: 10.1007/s10802-020-00766-w
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioral Trajectories of 2 to 9 Years Old Children Born to Opioid-Dependent Mothers

Abstract: Maternal opioid use in pregnancy has increased dramatically. Knowledge about children’s longer-term emotional and behavioral development after prenatal opioid exposure is scarce. A regional sample of 89 opioid-exposed and 104 non-exposed comparison children were studied prospectively at ages 2, 4.5, and 9 years using the Strengths and Difficulties Questionnaire (SDQ) completed by primary caregivers. Across all childhood assessments, opioid-exposed children obtained significantly higher total difficulties score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
(90 reference statements)
2
13
0
Order By: Relevance
“…The positive effect of non-intrusive and nurturant parenting and a culturally enriched environment on children's language development seen here is especially important considering the developmental trajectory of these high-risk children. A recent study using the same population of children studied here has shown persistent developmental risks across multiple domains of psychosocial development [14]. These findings combined with those from the present study highlight the need for early identification and support for these children and their families to optimize these children's developmental opportunities.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The positive effect of non-intrusive and nurturant parenting and a culturally enriched environment on children's language development seen here is especially important considering the developmental trajectory of these high-risk children. A recent study using the same population of children studied here has shown persistent developmental risks across multiple domains of psychosocial development [14]. These findings combined with those from the present study highlight the need for early identification and support for these children and their families to optimize these children's developmental opportunities.…”
Section: Discussionsupporting
confidence: 74%
“…The second reference or control group of children recruited were not exposed to opioids, and were randomly selected from the hospital booking schedule during the same period. The reference or non-exposed (NE) group consisted of 110 infants (48 male) who were born into families whose socioeconomic profiles were representative of the regional population at the time of birth [11,14]. Mothers from both groups were recruited during the third trimester or at birth.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second reference or control group of children recruited were not exposed to opioids, and were randomly selected from the hospital booking schedule during the same period. The reference or nonexposed (NE) group consisted of 110 infants (48 male) who were born into families whose socioeconomic profiles were representative of the regional population at the time of birth [11,14]. Mothers from both groups were recruited during the third trimester or at birth.…”
Section: Study Participantsmentioning
confidence: 99%
“…Existing evidence suggests increased risks for a range of adverse neonatal outcomes, including poorer fetal growth and Neonatal Abstinence Syndrome, as well as the possibility that child risks may extend into early and middle childhood [3,[8][9][10][11][12][13]. However, longer term follow-up studies are limited and inconclusive [10,12,14].…”
Section: Introductionmentioning
confidence: 99%